Dielectric Response Triggered by a Non-ferroelectric Phase Transition in Poly(Vinylidene Fluoride)/Poly(Ethylene Glycol)/Halloysite Composites. Issue 12 (21st August 2020) - Wang, Wei; Li, Hairong; Zhao, Jinchao; Tu, Junyang; Wu, Wenqi; Luo, Zhiping; Jiang, Ming; Huang, Leping
Abstract: Thermoresponsive dielectric materials have attracted the interest of researchers as they exhibit very important application prospects in stimuli-responsive smart devices. In this contribution polyethylene glycol (PEG), impregnated in halloysite nanotubes (HNTs), was incorporated into poly(vinylidene fluoride) (PVDF) for tailoring the thermoresponsive dielectric properties based on a non-ferroelectric phase transition. The PVDF/PEG/HNTs displayed a remarkable rise of dielectric constant between 20 and 30 °C. The mechanism is related to the enhanced orientational polarization effect triggered by the solid–liquid phase transition of the PEG. This make it possible to design stimuli-responsive smart materials through a simple, low-cost and efficient strategy. The present work provides an alternative and innovative routine for tailoring thermal-induced dielectric behaviors via a non-ferroelectric phase transition by introducing PEG into a high-dielectric-constant polymer matrix.